2021
DOI: 10.21776/ub.jepa.2021.005.04.13
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan Produk Olahan Jahe di Kecamatan Jenawi Kabupaten Karanganyar (Studi Kasus Kelompok Wanita Tani Desa Sidomukti)

Abstract: This study aimed to analyzed development strategies that can be applied to ginger processed product in Jenawi District, Karanganyar Regency. Data collected by interview and field observation. Data was analyzed using the IE and SWOT matrix analysis. The Mukti Rahayu Women's Farmer Group was founded in 2009 to process emprit ginger production into instant ginger products and fill in the activities of housewives around the group environment. In addition, the formation of groups also aimed to improve the economic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 2 publications
1
6
0
Order By: Relevance
“…If the additional ingredients have a dark color, the resulting product will also be darker, as well as other qualities, the aroma will be more fragrant, the texture of the resulting bread will be more brittle/hard, the taste of the bread will become unpleasant as the additional ingredients increase. So that acceptance is decreasing, this is in accordance with the opinions of several researchers below [30][31][32][33][34][35][36].…”
Section: The Process Of Making Black Rice Substitute Breadsupporting
confidence: 88%
See 1 more Smart Citation
“…If the additional ingredients have a dark color, the resulting product will also be darker, as well as other qualities, the aroma will be more fragrant, the texture of the resulting bread will be more brittle/hard, the taste of the bread will become unpleasant as the additional ingredients increase. So that acceptance is decreasing, this is in accordance with the opinions of several researchers below [30][31][32][33][34][35][36].…”
Section: The Process Of Making Black Rice Substitute Breadsupporting
confidence: 88%
“…This is because the additional ingredients have unpleasant properties and are close to the taste of black sticky rice. This makes the resulting sweet bread even less delicious and the panelists show that their assessment of the sensory quality of the sweet bread taste is increasingly bad [32][33][34], [46], [54][55][56][57].…”
Section: Quality Of Black Rice Substitute Breadmentioning
confidence: 99%
“…The more the number of additives produced, the darker the color, the more fragrant the aroma, the more brittle the texture of the candy produced, and the more unpleasant the taste of the candy with the increase in the additives. So the acceptance is decreasing [20], [31]- [34] b. The quality of the Candy…”
Section: A the Process Of Making Candymentioning
confidence: 99%
“…However, the candy with FS152 formulation or with the addition of 6.6% of cinnamon extract, 3.45% of ginger extract. And 4.95% of tempe flour is the most delicious and the most preferred by the panelists [20], [32], [47]- [50] The preference test showed that the increase in the additive ingredients of cinnamon extract, ginger extract and tempe flour showed less preference. This was due to the darker quality of the candy.…”
Section: A the Process Of Making Candymentioning
confidence: 99%
See 1 more Smart Citation